2018
DOI: 10.3389/fphar.2018.00590
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Porcine Full-Thickness Burn Hypertrophic Scar Model and Investigation of the Effects of Shikonin on Hypertrophic Scar Remediation

Abstract: Hypertrophic scars formed after burns remain a challenge in clinical practice. Development of effective scar therapies relies on validated animal models that mimic human hypertrophic scars. A consistent porcine full-thickness burn hypertrophic scar model has yet to be developed. We have previously reported that Shikonin induces apoptosis and reduces collagen production in hypertrophic scar fibroblasts in vitro and may therefore hold potential as a novel scar remediation therapy. In this study, we aimed to vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…This model of hypertrophic scarring after deep dermal partial-thickness burn injury can be used to further understand the pathophysiology of burn wound healing and scar formation as well as for the testing of various agents which could potentially improve the outcome of the burn wound. Another report demonstrated the reproducible burn hypertrophic scar model using the Bama miniature pig by applying a homemade heating device for 35 seconds followed by debridement surgery [45]. This model has displayed a similar macroscopic, histologic, and biologic criteria of burn wound compared to the human hypertrophic scars.…”
Section: Pigmentioning
confidence: 99%
“…This model of hypertrophic scarring after deep dermal partial-thickness burn injury can be used to further understand the pathophysiology of burn wound healing and scar formation as well as for the testing of various agents which could potentially improve the outcome of the burn wound. Another report demonstrated the reproducible burn hypertrophic scar model using the Bama miniature pig by applying a homemade heating device for 35 seconds followed by debridement surgery [45]. This model has displayed a similar macroscopic, histologic, and biologic criteria of burn wound compared to the human hypertrophic scars.…”
Section: Pigmentioning
confidence: 99%
“…180,181 Both therapies also led to an increase in angiogenic markers coupled with a decrease in fibrotic markers such as TGF-b1. [182][183][184] Rapp et al compared these two kinds of products in a porcine model of hypertrophic scar after burning. They reported very similar results, that is, a rapid reduction of erythema and a decrease in scar thickness.…”
Section: Plastic Surgery Indicationsmentioning
confidence: 99%
“…10 Naturally, the Mini Bama pig, characterised by its small size, slow growth, good genetic stability and minor individual differences, has been proposed as a replacement for the red Duroc pig. 11 Studies have also shown that skin stratification, thickness and structure of the Mini Bama pig are similar to those of human skin. Recently, Deng et al 11 created a full-thickness dermal burn injury on the Guangxi Bama minipig that resulted in hypertrophic scars.…”
Section: Introductionmentioning
confidence: 96%
“…11 Studies have also shown that skin stratification, thickness and structure of the Mini Bama pig are similar to those of human skin. Recently, Deng et al 11 created a full-thickness dermal burn injury on the Guangxi Bama minipig that resulted in hypertrophic scars. Using this model, they confirmed the anti-scar effect of Shikonin, an active component extracted from Radix Arnebiae that has been studied to induce apoptosis and reduce the production of collagen in hypertrophic scar-derived fibroblasts.…”
Section: Introductionmentioning
confidence: 96%